New conception of the symbol: Charles Peirce's habit perspective in the semiotic analysis of culture in peruvian society - Loayza-Maturrano, Edward Faustino (2025)
A semiotic perspective that reconsiders the relationships between symbols, their mediation with language, and their nature is currently of interest in science. The aim of this study was to examine how symbolic mediation occurs by employing the epistemology of concepts as an analytical strategy. The design was a systematic scoping review based on, on the one hand, Charles Peirce's semiotic theory and, on the other hand, a discourse analysis through the conceptual parameterization of a symbolic corpus extracted from the cultural context of Peruvian society. The analysis relied on the concept of habit from Peircean semiotics to overcome traditional views on symbolization and thus explore the applicability of symbols in differentencoding systems. The results rejected the dominant concept of symbolic arbitrariness, as it was determined that symbols in contemporary Peruvian society depend on habitual use to establish connections between meanings and signifiers. Furthermore, parameterization was proposed as a classification method for linguistic and non-linguistic systems, opening a new horizon for future research in this area. The conclusion emphasized the indispensable role of culture in shaping types of communicative mediation, all of which deepens our understanding of the interaction between language, culture, and symbolism, and proposes a new conception of the symbol.